Purging the Past and Gauging the Future: Stage Puritans as Manifestations of Religious Trauma in Restoration Comedies Adapted from European Sources (1660-1689) - Alice Marion-Ferrand (XVII-XVIII)
This paper focuses on five Restoration comedies with religious concerns composed between Charles II’s return to England and the Glorious Revolution, and adapted from French, Spanish and English (Elizabethan and Jacobean) sources: The Law Against Lovers (1663) by William Davenant, Tartuffe or the French Puritan (1670) by Matthew Medbourne, Sir Patient Fancy (1678) by Aphra Behn, The Spanish Fryar, or the Double-Discovery (1681) by John Dryden, and Sir Courtly Nice, or It Cannot Be (1685) by John Crowne. Looking at this corpus through the prism of religious figures, in particular that of the stage Puritan, this paper aims to show how Restoration comedies both deal with the trauma of the Interregnum and use its memory to question ongoing and potentially upcoming religious troubles. It interrogates the cathartic function of these comedies, the Restoration updating of the figure of the stage Puritan, and suggests the existence of a continuum between stage Puritans and stage Catholics that created an underlying network of meaning for Restoration audiences.